Pressure loss prediction of gaseous flow in a conduit-system of microchannel heat exchanger - Shintaro MURAKAMI; Kaoru TOYODA; Yutaka ASAKO (Nihon Kikai Gakkai ronbunshu, 2020)
Three methods for predicting pressure loss of gaseous flow in a conduit-system of microchannel heat exchanger are proposed and discussed. In the experiment, the heat transfer plate which is the core of the heat exchanger has 34 rectangular microchannels. The microchannels are 330 μm in width, 200 μm in depth and 20 mm in length. The working fluid is air at room temperature, which is compressed to flow in the heat exchanger and flows out to atmospheric surroundings. The static pressures were measured at the inlet and outlet of the conduit-system. The conduit-system, namely, the heat exchanger and the piping system, includes several factors of pressure loss such as pipe friction, sudden expansion or contraction at the joints of piping system, besides the conventional loss at the heat exchanger core. These additional losses cannot be ignored because the hydraulic diameters of piping system tend to be small for microchannel heat exchangers. The prediction methods are formulated with the assumption that the pressure loss coefficients (such as pipe friction factor) have the same value of those of incompressible flow. One of the methods is simply formulated assuming isothermal flow and constant densities in each conduit-element, and another one is based on one-dimensional adiabatic flow theory. These two methods adopted pressure loss correlation of incompressible flow as approximation. The third method adopted modified pressure loss correlation where the essence of pressure loss is considered as internal heat generation by dissipation, and total pressure loss is calculated based on isobaric curves on h-s chart using entropy increase by the heat generation. When the measured outlet pressure is used as initial value of prediction, the third method gives the best prediction of static pressure difference between the inlet and outlet of the conduit-system within 3.9% difference from the experiment in the range of 371-1460 of channel Reynolds number.